BLOOD GROUPS DISTRIBUTION IN IRAN - D.D. Farhud; A. Eftekhari (Tehran University of Medical Sciences, 1994)
Blood samples (291857) from 24 provinces of Iran were tested for ABO and Rh groups. The Rh complexes as well as Kell, Duffy, Kidd, Lutheran, Kp and Xg blood groups were tested only on a part of the material from Tehran. Results show a great deal of heterogeneity for ABO and Rh groups in various provinces of Iran. The calculated gene frequencies are compared with those of other investigations in Iran and those in Europe.